EFEKTIVITAS EKSTRAK BIJI JINTAN HITAM (Nigella sativa Linn.) TERHADAP INFEKSI BAKTERI STREPTOCOCCUS AGALACTIAE PADA IKAN NILA (Oreochromis niloticus Linn.) - Gustiana, Gustiana; Rantetondok, Alexander; Zainuddin, Elmi Nurhaidah (Torani Journal of Fisheries and Marine Science, 2015)
Black Cumin Seeds (Nigella sativa L.), commonly known as black seed, have been used in traditional medicine.Streptococcus agalactiae is a Gram-positive bacteria that causes the disease Streptococcosis in nile tilapia(Oreochromis niloticus L.). This study aims to find the bioactivity of black cumin seeds (N. sativa L.) againstbacterial pathogens in nile tilapia (O. niloticus L.). The research activities include preparation of samples blackcumin seeds (N. sativa L.), extraction with kinetic maceration method using solvents from different polarity (nhexane,ethanol and methanol), determination of antibacterial activity and minimum inhibition concentration(MIC) by agar diffusion method. The results of antibacterial activity against S. agalactiae of pathogenic bacteriashowed that the highest activity was performed by semi-polar extract ethanol (inhibition zone diameter of 15.33mm), followed by extract polar methanol with inhibition zone diameter of 12.67 mm. Extract non-polar nhexanedid not show any activities against the bacterial test. Determination of the minimum inhibitoryconcentration (MIC) of ethanol extract against S. agalactiae showed a value of 250 ppm. Keywords: Antibacteria, Streptococcus agalactiae, Nile Tilapia (Oreochromis niloticus L.), Nigella Sativa L